Entrepreneurship and Job Creation in Jordan: Challenges and Prospects for Start-ups - Mutaz Minwer Halal Alharbi (Journal La Bisecoman, 2020)
The aim of this article is to assess entrepreneurship activities in Jordan and present how start-ups reduce unemployment. The article also explores the challenges that start-ups face and how such challenges hinder entrepreneurs from engaging in business smoothly. The sample of the study comprises two hundred start-ups distributed in different regions in the country. The method of analysis employed is primarily descriptive statistics in the form of frequencies. Moreover, the binary logit model is used to check the prospects of self-employment and business creation attitudes among youth. The findings of the study reveal that entrepreneurship is one of the main strategies for creating jobs in Jordan, and it contributes to the overall growth of national economy. The study also reveals that the major challenges to engage in start-ups are related to financing and fundraising, regulations of taxation and interpretations of laws. The study also identified a considerable lack of entrepreneurial training at the early stages of business creation.